Love Kills and Dies : Oscar Wilde’s Poetic Meditations of Mortality - Aflecht, Ada (My University, 2024)
This thesis studies the themes of love and death in Oscar Wilde’s (1854–1900) poems, including “Requiescat” (1881) and “The Ballad of Reading Gaol” (1898). Through close reading, the thesis examines how the poet employs figurative language to support the themes of love and death. More specifically, this thesis focuses on the use of metaphors, imagery, and repetition as some of the author’s literary devices to highlight love and death in his poetry. My analysis delves into Wilde’s personal life and discusses how the loves and deaths personally experienced by him have influenced his works as a poet. Through my study of how Wilde utilises literary devices in supporting the recurrent themes of love and death, I probe how the devices allow the readers to visualize the themes in the texts. In addition, I explore various connotations associated with the themes, transcending the confines of solely romantic love or physical demise.
Keywords: Oscar Wilde, poetry, “The Ballad of Reading Gaol,” “Requiescat,” figurative language, love, death